Pengaruh Supervisi dari Pimpinan dan Komunikasi Internal Organisasi Terhadap Kepuasan Kerja Karyawan Kinderfield Highfield School Bekasi - Waliman, Sholeh; Ariandi, Fajri; Fitra, Safrezi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Supervision from leaders and internal organizational communication are important factors that can influence the level of employee job satisfaction. In an effort to increase job satisfaction, a supportive work environment is needed, where efficient supervision and communication are the keys to success. This study aims to analyze the influence of supervision from leaders and internal organizational communication on employee job satisfaction at Kinderfield Highfield School Bekasi. This research method uses a quantitative approach with a saturated sampling technique. The data collection technique was carried out by distributing questionnaires to 97 respondents. Data processing was carried out using the Statistical Product and Service Solution (SPSS) version 25 program. The results of the study indicate that partially the Supervision variable from Leaders (X1) has an influence on Employee Job Satisfaction (Y), and the Internal Organizational Communication variable (X2) has an influence on Employee Job Satisfaction (Y). Simultaneously, Supervision from Leaders (X1) and Internal Organizational Communication (X2) have influence on Employee Job Satisfaction (Y).